1998
DOI: 10.1046/j.1365-2125.1998.t01-1-00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Single dose and steady state pharmacokinetics and pharmacodynamics of the ACE‐inhibitor imidapril in hypertensive patients

Abstract: Aims To investigate the pharmacokinetic profile of the ACE-inhibitor imidapril in 10 hypertensive patients after a first single dose (10 mg ) and after 28 days therapy with imidapril 10 mg once daily. Methods C max , t max , t 1/2 and AUC of imidapril and imidaprilat were obtained. ACE-activity and arterial blood pressure during imidapril were corrected by a preceding placebo-investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast to calculated predictions, there was a significant decrease in I 24 and AUC 0–24 from day 1 to day 7 of repeated daily administrations. Studies in people and dogs have shown minimal to no cumulative effects on ACE inhibition with repeated administration . However, the significant decrease in I 24 and AUC 0–24 were unexpected.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to calculated predictions, there was a significant decrease in I 24 and AUC 0–24 from day 1 to day 7 of repeated daily administrations. Studies in people and dogs have shown minimal to no cumulative effects on ACE inhibition with repeated administration . However, the significant decrease in I 24 and AUC 0–24 were unexpected.…”
Section: Discussionmentioning
confidence: 98%
“…Because t max of imidaprilat and enalaprilat is longer than 2 hours (Table II), absorption and de‐esterification of imidapril and enalapril occurred during the dialysis sessions and may have affected plasma concentrations of their active metabolites in this study. However, such contributions are likely minor for the difference of arterial drug concentrations between imidaprilat and enalaprilat because the t max of the 2 drugs are relatively similar 9,16 (Table III). On the other hand, the prodrug still remains in the blood during the dialysis session, and it may be eliminated by the dialysis, which consequently affects the concentration profiles of active metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…We used high‐performance liquid chromatography (HPLC) to measure plasma drug concentration 9,10,16 . A 0.1‐mL volume of 0.25 M hydrochloric acid and 1 mL of 30 mM 1‐decansulfonate were added to each plasma sample (0.5 mL) and vortexed well.…”
Section: Methodsmentioning
confidence: 99%